Material Culture-Specific Items in İstanbul: Hatıralar ve Şehir and Translation Issues into English - Soliman, Heba; Sudartinah, Titik (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study investigates the translation procedures employed in rendering material culture items from Turkish into English in Orhan Pamuk's memoir İstanbul: Hatıralar ve Şehir (2003), as translated by Maureen Freely in Istanbul: Memories and the City (2006). Drawing on Vinay and Darbelnet's (1995) taxonomy of translation procedures and Newmark's (1988) classification of culture-specific items, the study adopts a mixed-methods research design, combining qualitative textual analysis with quantitative frequency measurement. A corpus of 50 purposively selected material culture items was compiled and categorized into four Newmark-derived domains: houses and towns (72%), food and drink (16%), transport (10%), and clothing (2%). The analysis reveals that literal translation (32%) and borrowing (28%) constitute the predominant strategies, followed by modulation (16%), equivalence (10%), adaptation (6%), generalization (4%), and marginal occurrences of loss and explicitation (2% each). These findings suggest that the translator prioritized linguistic transparency and cultural fidelity through strategies that either preserve source-culture specificity or facilitate target-language comprehension. Implications for translator training, cultural mediation, and cross-cultural literary reception are discussed.